Islamic Social Finance: A Bibliometric Analysis - Nurizal Ismail; Siti Aisyah (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2021)
Islamic social finance was discussed in 2013 by IRTI-IDB as a new spirit in solving the economic problem by allocating funds for humanitarian social works by using zakah, infaq, sadaqah, waqf, qardh al-hasan, and Islamic micro-insurance and Islamic microfinance. Islamic social finance has many imperatives to solve socio-economic problems. Therefore, it is needed to study the current state of Islamic social finance research to date. Thus, the study attempts to explore the status of Islamic social finance literature using bibliometric analysis by identifying statistics number of publications year by year, influential aspects, visualization of co-occurrence of keywords, and data texts related to the topic of Islamic social finance by using VOSviewer software. The finding of the study indicated that few articles discussed Islamic social finance. The most discussion of Islamic social finance was in 2019, which tried to handle the issues of the Covid-19 pandemic. Consequently, the journals that contributed the most to the study of Islamic social finance were al-Shajarah and the International Journal of Islamic and Middle Eastern Finance and Management. IIUM and INCEIF have contributed the most in the literature related to Islamic social finance from the author's affiliation. Malaysia is the most contributing country in writing Islamic social finance literature. Furthermore, the most selected keywords of Islamic finance research are Islamic social finance, maqasid syariah, value-based intermediation, sustainable development goals, and waqf. For the most co-occurrence text data, six clusters discussed the role of Islamic social finance in Covid-19, culture and country case on Islamic social finance, sustainable development goals, ecosystem, and maqashid syari’ah.